2019
DOI: 10.1177/0145561319875438
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Adenoid Hypertrophy, Tympanometry Findings, and Viscosity of Middle Ear Fluid in Chronic Otitis Media With Effusion, Southern Oman

Abstract: Otitis media with effusion is a common cause of diminished hearing in children younger than 12 years. Hypertrophy of adenoids is one of the commonest etiologies of this condition. It has been mentioned that with increased size of the adenoid tissue, the more likely the incidence of fluid in the middle ear. The aim of this study was to find whether there is a correlation between adenoid size, tympanometric findings, and type of fluid in the middle ear irrespective of disease duration. This is a prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…It is a multifactorial disorder; eustachian tube (ET) dysfunction, parental smoking, family history, increased number of siblings, and microbial, immunologic, genetic, and environmental factors might have a contribution to its pathogenesis 5 . It can lead to hearing loss, language, and developmental problems 5,6 . OME mainly affects children between the ages of 1 to 6 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a multifactorial disorder; eustachian tube (ET) dysfunction, parental smoking, family history, increased number of siblings, and microbial, immunologic, genetic, and environmental factors might have a contribution to its pathogenesis 5 . It can lead to hearing loss, language, and developmental problems 5,6 . OME mainly affects children between the ages of 1 to 6 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they reported the correlation between grade IV adenoid hypertrophy and middle ear effusion viscosity. 12 Another study by Nwosu et al 13 found that a higher grade of adenoid size was associated with an increased incidence of OME. 13 In addition to adenoid size, the correlation between the adenoids and OME may be caused by microbial reservoirs for ascending infection to the middle ear.…”
Section: Discussionmentioning
confidence: 97%
“… 11 Several studies have reported on the association between adenoid hypertrophy and OME. 12 13 However, a study by Durgut and Dikici concluded that adenoid size and location were not associated with hearing thresholds and the duration of OME. 14 Several studies found an association between allergic rhinitis and OME in children in subtropical countries 15–17 ; however, there are several differences in the main sensitisers in allergic patients living in tropical urban environments and subtropical areas.…”
Section: Introductionmentioning
confidence: 98%
“…Skoloudik et al also noted that the relation between adenoids and torus tubarius is much more important than the volume of lymphoid tissues [ 15 ]. Moreover, Abdel Tawab&Tabook in their recent study reported the highly significant correlation between adenoid size and mucoid nature of middle ear fluid [ 25 ]. However, the role of adenoids in the pathogenesis of OM is more sophisticated due to infectious and inflammatory aspects.…”
Section: Discussionmentioning
confidence: 99%